(‐)‐Epicatechin regulates blood lipids and attenuates hepatic steatosis in rats fed high‐fat diet. Issue 11 (29th August 2017) - Cheng, Hui; Xu, Na; Zhao, Wenxia; Su, Jingjing; Liang, Mengru; Xie, Zhongwen; Wu, Xianli; Li, Qinglin
Abstract : Scope: (‐)‐Epicatechin (EC) is a natural flavanol monomer found in cocoa, green tea, and a variety of other plant foods. In this study, effects of EC on blood lipids and hepatic steatosis, and the underlying mechanisms were investigated. Methods and results: A hyperlipidemic rat model was induced by high‐fat, high‐cholesterol diet. EC was then administrated to the animals by gavage at doses of 10, 20, 40 mg/kg body weight (BW) for 12 weeks. Simvastatin was included as a positive control. The results showed that EC significantly reduced total cholesterol, LDL cholesterol and triglyceride, alleviated liver fat accumulation, while increased HDL cholesterol, in hyperlipidemic rats. EC also reduced lipid peroxidation, inhibited the pro‐inflammatory cytokines, and lowered serum AST and ALT. The potential molecular mechanisms of EC underlying these effects were proposed to be associated to regulating Insig‐1‐SREBP‐SCAP pathway, and other lipid metabolic related genes including LXR‐α, FAS, and SIRT1. Conclusion: EC effectively improved blood lipid profile and protected liver from accumulating excessive fat in hyperlipidemic rats. The results shed a light on the potential role of EC as a promising natural product in preventing hyperlipidemia and nonalcoholic fatty liver disease. Abstract : This study was designed to test if epicatechin (EC) could alter blood lipids and prevent lipid accumulation in liver, and to explore the underlying mechanisms in a high‐fat, high‐cholesterol fed rat model. The results showed that EC significantly reduced total cholesterol, LDL cholesterol and triglyceride, while increased HDL cholesterol, in hyperlipidemic rats. EC effectively alleviated liver fat accumulation, reduced lipid peroxidation, inhibited the pro‐inflammatory cytokines, and lowered serum AST and ALT (two sensitive indicators of liver damage). The potential molecular mechanisms of EC underlying these effects were proposed to be associated to lipid metabolic related genes. The results shed a light on the potential role of EC as a promising natural product in preventing hyperlipidemia and non‐alcoholic fatty liver disease.